Eddison Walters Modern Economic Analysis Theory: Building on the Eddison Walters Risk Expectation Theory of The Global Financial Crisis of 2007 and 2008 - Walters, Eddison T. (Archives of Business Research, 2020)
The results of several recent studies called the analysis of economic data from the United States real estate industry preceding the Global Financial Crisis of 2007 and 2008 into question. Advancement of technology is a disruptive force throughout the economy today. The speed at which technology continues to evolve has resulted in significant changes throughout the entire economy around the world. As technology continue to evolve, there is no question technology disruption will continue to occur. Economist can no longer rely solely on backward looking historical data when conducting economic analysis. The evolution of the global economy require an understanding of the impact of advancement in technology occurring throughout the economy as researcher conduct analysis of data to draw conclusions. The result of recent studies led to the development of “Eddison Walters Modern Economic Analysis Theory”. Data analysis suggesting the false conclusion of the existence of a real estate bubble in the United States real estate market preceding the Global Financial Crisis of 2007 and 2008 was presented in Walters and Djokic (2019). Nonlinear regression analysis for correlation of variables in Walters (2019) resulted in 194.041 Mean Dependent Variable, 0.989 Adjusted R-square, 5.908 Square Error of Regression, and 488.726 Sum-of-Square Residual for the independent variable of “advancement in technology”, and the dependent variable of “home purchase price” preceding the Global Financial Crisis of 2007 and 2008. Walters (2019) concluded advancement in technology was the most significant factor causing home prices to increase preceding the Global Financial Crisis of 2007 and 2008. Overwhelming evidence led the researcher to conclude, the failure to consider the impact of advancement in technology in data analysis was the most significant error responsible for causing data analysis distortion leading to the false conclusion of the existence of a real estate bubble preceding the Global Financial Crisis of 2007 and 2008 (Walters, 2020). The researcher proposed “Eddison Walters Modern Economic Analysis Theory” in the current study. The goal of the new theory is to prevent potential error in data analysis resulting in data distortion due to the failure to consider the impact of advancement in technology on the data when conducting economic research in the future.